Inferiority Complex in F. Scott Fitzgeralds The Great Gatsby - ITA HUSNIYATI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2019)
ABSTRACT Inferiority Complex in F. Scott Fitzgerald’s The Great Gatsby Name : Ita Husniyati Reg. Number : 1320154024 Study Program / Year : S1 English Literature / 2013 Faculty : Language and Arts Institution : Surabaya State University Advisor : Hujuala Rika Ayu SS., M. Pd. The Great Gatsby, by F. Scott Fitzgerald is a classic story of the 20th century. Social status at that time was very influential on the lives of people in America which have significant differences in social classes, especially in terms of socialization. As a result of the differences in social class, there are many problems, whether in social or economic status. This study focuses on how the two characters in The Great Gatsby reflect inferiority complex and what drives the characters to have an inferiority complex. Inferiority complex is the feeling of inferiority is the basic factor of what Alfred Adler refers to as the conflict, included inferiority complex; because this feeling is, happen to the psychological characteristics of person who have bad experience in their life. The first problem talks about how Gatsby and Daisy reflect inferiority complex. The second is what drives Gatsby and Daisy to have an inferiority complex. To answer the problems, this study uses the theory of individual psychoanalytic by Alfred Adler and uses his inferiority concept to analyses Gatsby and Daisy’s problem. The result of the study shows that the inferiority complex is happening to Gatsby in reaching for his ambition. He does everything he can to make his life change which was originally nothing and become known. This feeling made him succeed in achieving his goal of getting wealth, but not only wealth became his goal, but love was also a top priority in his life. While Daisy wants to get everything in her life. She is a cunning woman, she uses her inferiority to protect herself and keep her surrounded by wealth. Therefore inferiority complex is a very detrimental thing for those who experience, as successful as anything he gets from this feeling will also fall later on. Key words: Inferiority complex, individual psychoanalytic, social classes, the Great Gatsby. Gatsby, Daisy. ABSTRAK Inferiority Complex in F. Scott Fitzgerald’s The Great Gatsby Name : Ita Husniyati Reg. Number : 1320154024 Study Program / Year : S1 English Literature / 2013 Faculty : Language and Arts Institution : Surabaya State University Advisor : Hujuala Rika Ayu SS., M. Pd. The Great Gatsby, oleh F. Scott Fitzgerald adalah kisah klasik dari abad ke-20. Status sosial pada waktu itu sangat berpengaruh pada kehidupan orang-orang di Amerika yang memiliki perbedaan signifikan dalam kelas sosial, terutama dalam hal sosialisasi. Akibat perbedaan kelas sosial, ada banyak masalah, baik dalam status sosial maupun ekonomi. Studi ini berfokus pada bagaimana dua karakter dalam The Great Gatsby mencerminkan inferiority complex dan apa yang mendorong karakter untuk memiliki inferiority complex. Inferioriti yang kompleks adalah perasaan inferioritas yang merupakan faktor dasar dari apa yang disebut Alfred Adler sebagai konflik, termasuk kompleks inferioritas; karena perasaan ini, terjadi pada karakteristik psikologis orang yang memiliki pengalaman buruk dalam hidup mereka. Masalah pertama berbicara tentang bagaimana Gatsby dan Daisy mencerminkan inferiority complex. Yang kedua adalah apa yang mendorong Gatsby dan Daisy untuk memiliki kompleks inferioritas. Untuk menjawab permasalahan, penelitian ini menggunakan teori psikoanalitik individu oleh Alfred Adler dan menggunakan konsep inferioritasnya untuk menganalisis masalah Gatsby dan Daisy. Hasil penelitian menunjukkan bahwa inferiority complex terjadi pada Gatsby dalam meraih ambisinya. Dia melakukan semua yang dia bisa untuk membuat perubahan hidupnya yang semula tidak ada dan menjadi dikenal. Perasaan ini membuatnya sukses dalam mencapai tujuannya untuk mendapatkan kekayaan, tetapi tidak hanya kekayaan yang menjadi tujuannya, tetapi cinta juga menjadi prioritas utama dalam hidupnya. Sementara Daisy ingin mendapatkan segalanya dalam hidupnya. Dia adalah wanita yang licik, dia menggunakan inferioritasnya untuk melindungi dirinya sendiri dan membuatnya tetap dikelilingi oleh kekayaan. Oleh karena itu inferiority complex adalah hal yang sangat merugikan bagi mereka yang mengalami, sesukses apapun yang ia dapatkan dari perasaan ini juga akan jatuh kemudian hari. Kata kunci: inferioritas yang kompleks, psikoanalitik individu, kelas sosial, Great Gatsby. Gatsby, Daisy.